Bioethical foundations for rehabilitation in patients with hip fracture. (RIAF. International Journal of Physical Activity, 2024)
Hip fractures are a causeof disability and morbidity in theelderly population, is defined as the loss of the continuity solution of the bone tissue of theregions of the head, femoral neck, and regionintertrochanteric. They are classified as intracapsular and extracapsular. It is important to distinguish them by the impact on the irrigation of the femoral head. The clinical presentation includes groin pain and inability to bear weight on theaffected limb, pain may radiate to thedistal femur. Physical examination may includeobserve shortening and external rotation of theaffected limb. The present researchreveals the role of health professionalsin compliance with the principles of themedical ethics in the daily actions of theRehabilitation specialty in patients with hip fracture.
Keywords: Hip fracture; Medical ethics; rehabilitation